AN INVESTIGATION OF AGNEZ MO’S CONTROVERSIAL STATEMENT ON ONLINE NEWS TEXT - Rahma Deni; Didin Nuruddin Hidayat (p-ISSN 2356-0576, 2021)
Along with the growth of social media, information is increasingly easy to be obtained and accessed. When receiving information, social media users tend to take information for granted without realizing false arguments. This descriptive qualitative study with critical discourse analysis design is aimed to provoke the readers of the online news to analyze the discourse redaction used by the media. Thus, they might understand the real point inside the news. This study centers on analyzing the news reduction of Liputan6.com about Agnez Mo controversial statement entitled “Agnez Mo dan 6 Reaksinya Soal Kontroversi Tak Punya Darah Indonesia”. Further, van Dijk’s critical discourse analysis framework centered on text structure like macrostructure, superstructure, and microstructure was employed. The results of this study indicated that liputan6.com took a side on Agnez Mo. It can be seen from the news' redaction in which the writer attempts to attract people empathy and believe on Agnez that she is the victim on this issue.